Distribution and mating type characterization of chickpea blight (Didymella rabiei (Kov.) v. Arx) in Ethiopia - Gezahegne Getaneh (Elsevier, 2021)
We have assessed the distribution and mating type of chickpea blight (Didymella rabiei (Kov.) v. Arx) from a total of 350 and 272 fields in major chickpea (Cicer arietinum L.) growing areas of Ethiopia for two consecutive cropping seasons 2017 and 2018, respectively. The prevalence of D. rabiei was 20 % for the year 2017 and 7% for 2018. Severity range of 2−9 and incidence of 10–100 % were recorded for both seasons in only 7–20 % of the assed fields. Field prevalence of 2017 and 2018 seasons were significantly different (df = 31; p < 0.001 and df = 31; p < 0.001, respectively). Similarly, the disease prevalence of both seasons was significantly different (df = 31; p < 0.001). The disease prevalence ratio frequency was highly deviated from (1:1) for both seasons (X2 = 213.62 p= <0.001; X2 = 144.36 p = 0.01). Genomic DNA of Representative samples were extracted from single spore culture and Mating type 1 (MAT1-1) specific primer SP21, Mating type 2 (MAT1-2) specific primer Tail 5, and a flanking region-specific primer Com1 assay were multiplexed in a single PCR reaction to determine the occurrence of D. rabiei mating type in Ethiopia. Out of 156 samples, only 15 samples were positive to MAT1-1 (∼10 %) with the ratio of 9:1. MAT 1−2 type was the most dominant and possibly the asexual reproduction of D. rabiei is the major type in Ethiopia. The result is important for Ascochyta blight management in breeding strategy.